Characteristics of Articles Published in the Journal of Institute of Medicine Nepal: A Cross-sectional Study - Shrestha, Lava; Singh, Yogendra P; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2022)
Introduction Scholarly journals publish various types of manuscripts. The objective of this study was to analyze the types of articles published in Journal of Institute of Nepal (JIOM Nepal) from 2019 April to 2021 April and describe their various characteristics. Methods Seven issues of JIOM Nepal published from April 2019 to April 2021 were analyzed for types of study, areas of medical science, the number of authors, gender of the primary author, contributing specialty, and author’s affiliation. Results Seven issues were published in the studied time period. In total, 139 articles were published, with a mean number of 19.8±4.4 articles per issue. More than half of the published articles were cross-sectional studies (93, 66.9%), followed by case reports (25, 17.9%). The majority of primary authors (94, 67.6%) were faculty from constituent campuses of the Institute of Medicine (IOM) Tribhuvan University. Thirty-eight 38 (27.3%) contributing authors were females. Fifty-three (38.1%) articles published were diagnosis-related. Authors from surgical specialties were the most common article contributors 67 (48.2 %), while basic science specialties contributed 13 (9.4%) publications Conclusion Cross-sectional studies were the most commonly published articles and surgical specialties published more than half of the articles. The majority of the articles were related to diagnosis. Greater efforts are needed to produce further progress of the journal. A mixture of original articles, reviews and case reports from different medical domains will be more interesting to the readers.